Analisis Perilaku dan Preferensi Mahasiswa terhadap Pengalaman Belanja Online dan Offline - Talita Ardra Widyadhana; Adelia Maileni Agustin; Dila Amalia; Firda Shauma Destiawan; Nabilla Hapsari Putri Fauzi; Stephanie Aurelia; Rama Wijaya Abdul Rozak (Pajak dan Manajemen Keuangan, 2024)
Shopping activities have become a dominant phenomenon in people's lives, one of which is among students. Students are an important segment in society, so they have become a shopping preference that deserves to be understood more deeply. The aim of this research is to analyze student behavior and preferences from shopping experiences. This research uses a descriptive quantitative method with data collection using a questionnaire with closed answers. The questionnaire was filled in by 152 respondents spread across various universities in Indonesia. The research results show that the e-commerce applications that are often used by students are Shopee and Tokopedia. Students prefer to shop through online shops because the prices offered are more affordable than conventional shops. Apart from that, if you shop via an online shop, the activity time is shorter and more efficient. In the online shop, the products offered are quite diverse and varied, and there are lots of promotions on offer so that they attract the attention of buyers. Online shops are used by students to buy fashion and skincare products because the products offered are more diverse compared to offline shops. Based on this data, it can be understood that students choose to shop through online shops using the Shopee and Tokopedia applications and choose to shop for fashion and skincare.